The effect of personality traits on collaborative consumption participation - Abu Hanifah Ayob; Zafir Khan Mohamed Makhbul (Penerbit Universiti Kebangsaan Malaysia, 2020)
The advancement of digital technology has refined the way traditional business operates. The new business model of collaborative consumption is not only novel, but potential customers are reluctant to participate. Who, then, is actually interested in embracing this new approach? To provide empirical evidence, this study attempts to examine the effects of the Big Five personality traits: agreeableness, neuroticism, extraversion, openness, and conscientiousness, on the propensity to participate in collaborative consumption. Drawing on the Student Behavior Survey 2019/2020 of 386 university students in Malaysia, we find that personality is not a strong predictor of collaborative consumption. In short, agreeableness increases the likelihood of participating in collaborative consumption and openness exhibits a negative effect; other traits have no effect.